2017
DOI: 10.3389/fevo.2017.00060
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Environmental Impact Assessment for Non-natural Reserve Areas: A Case Study of the Chaishitan Water Conservancy Project on Land Use and Plant Diversity in Yunnan, China

Abstract: Environmental impact assessment (EIA) before and after the establishment of a Water Conservancy Project (WCP) is of great theoretical and practical importance for assessing the effectiveness of ecological restoration efforts. WCPs rehabilitate flood-damaged areas or other regions hit by disasters by controlling and redistributing surface water and groundwater. Using Geographic Information System (GIS) and Composite Evaluation Index (CEI) in predictive modeling, we studied the degree to which a WCP could change… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…However, demands for the protection of water resources and ecological environments restrict development (Bian et al, 2022; Jiang et al, 2022). The interference of human activities on the ecological environments has been gradually amplified (Zeng et al, 2022; Zhu et al, 2017). Water conservancy projects are essential for flood control, water storage, sediment retention and enhancement of agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…However, demands for the protection of water resources and ecological environments restrict development (Bian et al, 2022; Jiang et al, 2022). The interference of human activities on the ecological environments has been gradually amplified (Zeng et al, 2022; Zhu et al, 2017). Water conservancy projects are essential for flood control, water storage, sediment retention and enhancement of agricultural production.…”
Section: Introductionmentioning
confidence: 99%
“…Water conservancy projects are essential for flood control, water storage, sediment retention, and enhancement of agricultural production. The interference of human activities on the ecological environments have been gradually amplified (Zeng et al, 2022;Zhu et al, 2017). Such projects enhance production and the standard of living in many regions.…”
Section: Introductionmentioning
confidence: 99%
“…From the year 2003, the TGD began to generate electric power, which could also contribute to the booming of the local economy [12,19]. Additionally, Zhu et al [20] found that the construction of dams in Yunnan province enriched the diversity of the local plants. There is also with evidence that construction of the TGD created favorable natural conditions for agricultural output located in the downstream regions [21].…”
Section: Introductionmentioning
confidence: 99%